2017
DOI: 10.1186/s13256-017-1252-0
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic spondylolisthesis and spinal cord compression in diffuse idiopathic skeletal hyperostosis: a case report

Abstract: BackgroundDiffuse idiopathic skeletal hyperostosis has long been regarded as a benign asymptomatic clinical entity with an innocuous clinical course. Neurological complications are rare in diffuse idiopathic skeletal hyperostosis. However, if they do occur, the consequences are often significant enough to warrant major neurosurgical intervention. Neurological complications occur when the pathological process of ossification in diffuse idiopathic skeletal hyperostosis extends to other vertebral ligaments, causi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
(7 reference statements)
1
12
0
Order By: Relevance
“…However, from the available literature, "All reported cases of thoracic spondylolisthesis have occurred in people of Asian ethnicity [and] most of them were concomitant with lumbar spondylosis or diffuse idiopathic skeletal hyperostosis (DISH) [33]." In published cases with TS, the spinal imaging shows loss in or reversal of sagittal thoracic curvature at and surrounding the TS [33][34][35][36][37].…”
Section: Etiology and Demographicsmentioning
confidence: 99%
“…However, from the available literature, "All reported cases of thoracic spondylolisthesis have occurred in people of Asian ethnicity [and] most of them were concomitant with lumbar spondylosis or diffuse idiopathic skeletal hyperostosis (DISH) [33]." In published cases with TS, the spinal imaging shows loss in or reversal of sagittal thoracic curvature at and surrounding the TS [33][34][35][36][37].…”
Section: Etiology and Demographicsmentioning
confidence: 99%
“…In addition, DISH is a risk factor for the development of thoracic spondylotic myelopathy; 6 hence, there are sporadic reports of thoracic spondylotic myelopathy associated with DISH. 8 Because thoracic spondylotic myelopathy does not present with any upper limb symptoms, patients with coexisting lumbar spinal stenosis often have no enhanced tendon reflex of the lower limbs (PTR and ATR), and some patients have only symptoms caused by lumbar spinal stenosis alone, such as numbness and muscular weakness of the lower limbs. 9 Thus, caution should be exercised not to overlook thoracic spondylotic myelopathy.…”
Section: Discussionmentioning
confidence: 99%
“…He suggested that the facet joint laxity and disc degeneration were believed to be responsible for the development of thoracic spondylithesis. Takagi et al reported a case of thoracic spondylolisthesis and spinal cord compression in DISH [3] . He believed that DISH resulted in the fusion of several spinal segments, and the unfused segments were more vulnerable to segmental instability and development of spondylolisthesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of them were concomitant with lumbar spondylosis or diffuse idiopathic skeletal hyperostosis (DISH). [2,3] Here we report a case of thoracic degenerative spondylolisthesis-associated myelopathy in which the lower thoracic region was the only region involved and to discuss the mechanism of thoracic spine spondylolisthesis.…”
Section: Introductionmentioning
confidence: 99%